A 30-kWth moving-bed chemical looping system for hydrogen production. (April 2020) - Chen, Cetera; Chen, Chien-Hua; Chang, Ming-Hui; Lee, Hsiu-Hsia; Chang, Yu-Cheng; Wen, Tzeng-Wen; Shen, Cheng-Hsien; Wan, Hou-Peng
Highlights: Iron-based oxygen carriers were pneumatically circulated and reacted in a 30-kWth moving bed chemical looping system. The concentration of CO2 produced in the reducer was 95%, and H2 produced in the oxidizer reached 90%. Oxygen carriers were nearly completely oxidized by air in the combustor resulting in temperature increase. Parts of the oxygen carriers in the reducer were reduced to Fe, showing the integrating conversion rate of 61.5%. In the oxidizer, the oxygen carrier contained Fe3 O4, and the integrating conversion rate was 22.2%. Abstract: A 30-kWth moving-bed chemical looping system has been developed at the Industrial Technology Research Institute of Taiwan. In this system, methane is supplied as a fuel to a reducer, and steam enters an oxidizer to produce hydrogen under ambient pressure. An iron-based oxygen carrier is used and pneumatically transported in the system. In this study, a hydrogen production test was performed on the system, while the methane flow rate was 40 L/min according to the capacity requirement of a 30-kWth system, and the oxygen carrier circulation rate was 2100 g/min for 40-wt% Fe2 O3 content. The concentration of carbon dioxide produced in the reducer was 95 %, and the concentration of hydrogen produced in the oxidizer reached 90 %. Partially oxidized oxygen carriers then reacted with air in the combustor, leading to a temperature increase of approximately 120°C. The oxygen carriers in the reducer were reduced to Fe, and the integrating conversion rate was 61.5 %. In the oxidizer, the oxygen carrier contained Fe3 O4, and the integrated conversion rate was 22.2 %. 75 % of the oxygen carriers in the combustor exhibited a conversion rate of 5.3 %, indicating a nearly complete oxidation state. By conducting the hydrogen production test while effectively removing small particles of worn oxygen carriers from the system, the moving-bed chemical looping system was evaluated for the circulation and reaction of oxygen carriers. The system development experience will be used for system scale-up design.